2019
DOI: 10.1007/s00792-019-01106-7
|View full text |Cite
|
Sign up to set email alerts
|

Production of highly catalytic, archaeal Pd(0) bionanoparticles using Sulfolobus tokodaii

Abstract: The thermo-acidophilic archaeon, Sulfolobus tokodaii was utilized for the production of 20 Pd(0) bionanoparticles from acidic Pd(II) solution. Use of active cells was essential to form well-21 dispersed Pd(0) nanoparticles located on the cell surface. The particle size could be manipulated 22 by modifying the concentration of formate (as electron donor; e-donor) and by addition of 23 enzymatic inhibitor (Cu 2+ ) in the range of 14-63 nm mean size. Since robust Pd(II) reduction 24 progressed in pre-grown S. tok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…This process implicates a mechanism of carbon dioxide (CO 2 ) homeostasis in hydrothermal ecosystems as greigite is the major catalysts for CO 2 reduction (Gorlas et al, 2018). Another group of researchers used thermos-acidophilic archaea, Sulfolobus tokadaii for the reduction of Pd (II) to Pd (0) NPs in a redox reaction (Kitjanukit et al, 2019). In a latest study, mass scale production of superparamagnetic iron oxide (Fe 2 O 3 ) NPs has been achieved using Halobiforma sp.…”
Section: Archaea For the Synthesis Of Npsmentioning
confidence: 99%
“…This process implicates a mechanism of carbon dioxide (CO 2 ) homeostasis in hydrothermal ecosystems as greigite is the major catalysts for CO 2 reduction (Gorlas et al, 2018). Another group of researchers used thermos-acidophilic archaea, Sulfolobus tokadaii for the reduction of Pd (II) to Pd (0) NPs in a redox reaction (Kitjanukit et al, 2019). In a latest study, mass scale production of superparamagnetic iron oxide (Fe 2 O 3 ) NPs has been achieved using Halobiforma sp.…”
Section: Archaea For the Synthesis Of Npsmentioning
confidence: 99%
“…Platinum is a well-known chemical catalyst to accelerate Equation ( 1) [26]. Therefore, the two-phase Pt(IV) reduction reaction exhibited by active cells can be explained as the first slower enzymatic Pt(0) crystal nucleation phase followed by the second, faster Pt(0) crystal growth via autocatalytic Pt(IV) reduction [5,20]. In cell-free controls, the overall speed of abiotic reactions was greater but produced a few, visibly large Pt(0) aggregated particles.…”
Section: Hcooh → Co2 + H2mentioning
confidence: 99%
“…So far, the biological fabrication of metal NPs explored a range of life forms, such as bacteria, yeast, fungi, algae, and plants, for metal species such Au, Ag, Pd, Pt, Ni, Co, and Fe [3,4]. The size of biogenic metal NPs can be controlled by modifying conditions such as concentrations of electron donors and reaction inhibitors [5,6]. Among those microorganisms or plants as the template for NPs' production, a number of bacterial species possess the ability to reduce soluble metal species to zero-valent nanometal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a highly efficient and stable method for the removal of radioactive iodine ( 125 I) using D. radiodurans with biogenic Au nanoparticles has been reported [ 131 ], in which more than 3.7 MBq of 125 I was efficiently removed (>99%) within 30 min. More recently, the thermo-acidophilic archeon S. tokodaii 7 T (NBRC 100140) capable of synthesizing biogenic Pd(0) nanoparticles (mean diameter: 8.7 nm) showed four-fold increased Cr(IV) reduction with 2.0 mg Cr(VI)/L/h/Pd(0) compared to a commercial Pd/C catalyst [(0.5 mg Cr(VI)/L/h/Pd(0)] [ 136 ]. Another study also demonstrated efficient Cr(IV) reduction using Pd(0) nanoparticles synthesized by the acidophilic Fe 3+ -reducing bacteria Ac.…”
Section: Bioremediation Using Extremophilesmentioning
confidence: 99%